Arquivo selvagem: arte e violência na América Latina - Melissa Etelvina Oliveira Rocha (2019)
The file that is built here is one that emerges from the testimonies of the images. Now silenced and sometimes retaken - the memory evoked by those who align with discordance, produces artistic works as manifestoes and denunciations of abuses contained in the exercise of power and collaborates to elaborate a resistant imaginary thought. As the indomitable branches of the inevitable growth of a myrtle, overcoming the barbarity of an endless and constant civilizing process is the edge of an unreachable path. It is understood, in fact, that the construction of a Latin Wild File in this text is beyond a geographic location and closer to a mnemonic and imagery rescue: a polyphonic collection composed of a cut of fictitious breaths, historical events and works which are intertwined by violence